Badania opinii publicznej oraz doradztwo polityczne: teoria i praktyka - Zaręba, Agnieszka (Political Preferences, 2014)
The main purpose of this article is to present the role of public opinion polls and political consulting on Polish political scene. The article contains results of surveys made in most Polish regions in 2013 and 2014 years. Firstly, there is described theory of public opinion poll before elections and after them based on the literature of public opinion polls.. In this part reader either can find some information about how the public opinion polls are perceived from Polish citizens' perspective. Secondly, there is presented the role of political consul- ting on Polish political scene. The conclusion confirms that Polish citizens have perceived considerable influence of public opinion polls and political consulting in Polish public policy.